Structural, morphological, and magnetic characterization of bulk and thin films Y3Al5–xFexO12 (YAIG): From the perspective of aqueous sol–gel processing. Issue 9 (2nd September 2017) - Opuchovic, Olga; Culunlu, Serdar; Morkan, Ayse Uztetik; Morkan, Izzet Amour; Niznansky, Daniel; Garskaite, Edita; Beganskiene, Aldona; Kareiva, Aivaras
ABSTRACT: An aqueous sol–gel method was used for the preparation of bulk Y3 Al5– x Fe x O12 (yttrium aluminum–iron garnet, YAIG) with the composition of x = 0.0, 1.0, 2.0, 2.5, 3.0, 4.0, 5.0 and thin films with the composition of x = 0, 3.0, 4.0, 5.0. The dip-coating technique was used for the preparation of Y3 Al5– x Fe x O12 films on a silicon (Si) substrate. The phase composition and surface morphology of both bulk and coatings were determined and compared. The synthesized powder samples were investigated by X-ray diffraction analysis, infrared spectroscopy, scanning electron microscopy, and Mössbauer spectroscopy. The data provide evidence that some sol–gel-derived powder specimens consist of magnetically ordered component, while others show paramagnetic behavior depending on the composition of the product. It was also shown that sol–gel processing route could be successfully used for the preparation of mixed-metal YAIG thin films.